Urban transportation : planning, operation and management - Victor, D. Johnson; Ponnuswamy, S. (McGraw-Hill's AccessEngineering., 2012)
"Urban Transportation has become a subject of major interest for students, academia and practicing engineers in the government and private sector. So far, there is hardly any book available on the subject written by Indian authors covering the subject in the context of a developing country. In order to meet the demand, the authors have come together to pool their knowledge gained as a teacher and a practicing engineer respectively and write this book. This book has been prepared to fit in with the syllabus on Urban Transport and Public Transport taught at graduate level in various universities and Indian Institutes of Technology as well as Schools of Planning. At the same time, the book can be used as a reference book by practicing engineers and consultants. It covers the subject of planning for transportation in an urban area including basic principles and current practices. Special emphasis has been given to conditions in India and developing countries.".